An Empirical Study for Radio Frequency Identification (RFID) Adoptionby SMEs in the Taiwanese Information Technology (IT) Industry - Hsin Chen; Anastasia Papazafeiropoulou (Asian Academy of Management Journal, 2012)
Radio Frequency Identification (RFID) technology represents a common standard for data storage and retrieval that could improve collaboration and data sharing between non-competing organisations. With the advent of RFID, organisations have the opportunity to rethink how their organisation will operate and integrate in the supply chain. Especially for Small to Medium Sized Enterprises (SMEs), that they have limited resources adopting such an innovative technology (i.e. RFID) the adoption decision can be daunting. Literature indicates that SMEs that decide to go on with implementation have so far only a few guidelines from either private companies or public authorities regarding awareness on specific opportunities and risks. This research is therefore trying to explore in detail the factors that affect SMEs' RFID adoption in the Taiwan Information Technology (IT) manufacturing industry. We are employing Exploratory Factor Analysis (EFA) techniques and utilising a questionnaire survey in order to collect and analyse our data. After classifying the responding SMEs into three different adopters categories named ready adopter, initiator adopter and unprepared adopter using EFA technique our results show that each category has some specific adoption factors related to their unique situation. These are for ready adopters: cost and management, for initiator adopters: competitiveness and process efficiency and unprepared adopters: IT management difficulties, IT implementation difficulties and cost of implementation. A SMEs RFID adoption model is then proposed. It is anticipated that the findings of this research will not only enhance the research in RFID adoption in SMEs, but can also act as a reference for practitioners in the industry and researchers in the academic field.